Адміністративно-правова концепція здійснення державної митної справи: теорія та практика - Федотов, Олексій Павлович (My University, 2016)
Дисертацію присвячено науковому дослідженню питань теорії та практики адміністративно-правової концепції здійснення державної митної справи. Сформульовано поняття «адміністративно-правова концепція здійснення державної митної справи» – теоретико-методологічна основа правового регулювання процедур здійснення державного управління у митній сфері, яка містить: головний задум, систему керівних принципів, сукупність погоджених цілей та заходів модернізації митної справи, заплановані індикатори результату та індикатори успіху концепції. Досліджено динаміку інституційного забезпечення здійснення державної митної справи та сучасні тенденції системи органів митного спрямування Державної фіскальної служби України, встановлено особливості трансформації державної митної справи як складової зовнішньоекономічної діяльності держави та охарактеризовано становлення концепції державної митної справи у вітчизняній правовій науці. Окреслено проблемні аспекти та перспективи модернізації адміністративно-правової концепції здійснення державної митної справи на сучасному етапі державотворення з урахуванням світових тенденцій розвитку міжнародної торгівлі та потреб забезпечення національної безпеки. На підставі аналізу чинного законодавства України з питань державної митної справи надано конкретні пропозиції щодо розробки єдиного збалансованого підходу до правотворчості та правозастосування у сфері державної митної справи та розроблено науково обґрунтовану цілісну модель адміністративно-правової концепції здійснення державної митної справи.

Диссертация посвящена научному исследованию вопросов теории и практики административно-правовой концепции осуществления государственного таможенного дела. Сформулировано понятие «административно-правовая концепция осуществления государственного таможенного дела» – теоретико-методологическая основа правового регулирования процедур осуществления государственного управления в таможенной сфере, содержащая главный замысел, систему руководящих принципов, совокупность согласованных целей и мероприятий модернизации таможенного дела, запланированные индикаторы результата и индикаторы успеха концепции. Исследована динамика институционального обеспечения государственного таможенного дела и современные тенденции системы органов таможенного направления Государственной фискальной службы Украины, установлены особенности трансформации государственного таможенного дела как составляющей внешнеэкономической деятельности государства и охарактеризовано становление концепции государственного таможенного дела в отечественной правовой науке. Определены проблемные аспекты и перспективы модернизации административно-правовой концепции осуществления государственного таможенного дела на современном этапе создания государства с учетом мировых тенденций развития международной торговли и потребностей обеспечения национальной безопасности. На основании анализа действующего законодательства Украины по вопросам государственного таможенного дела представлены конкретные предложения по разработке единого сбалансированного подхода к правотворчеству и правоприменению в сфере государственного таможенного дела, разработана научно обоснованная целостная модель административно-правовой концепции осуществления государственного таможенного дела.

The thesis deals with a scientific study of theory and practice aspects of the administrative and legal concept of the customs procedures implementation. Formulated is the notion of «administrative and legal concept of the customs procedures implementation» as a theoretical and methodological base for a legal control of the government administration of customs procedures which includes: main idea, system of guiding principles, the whole of agreed objectives and means of the customs procedures modernization, planned indicators of results and the indicators of the concept success. The main elements of the administrative and legal concept of the customs procedures implementation have been determined which include: 1) the concept of legal control of the procedures governing establishment and re-organization of the customs bodies of the State Fiscal Service of Ukraine; 2) the concept of legal control of the technology applied for staffing the customs bodies; 3) the concept of legal control of the customs procedures. History of the institutional support of the state customs procedures and the current trends in the system of the customs authorities of the State Fiscal Service of Ukraine have been studied, specific features of the state customs procedures that make a component of the external economic activity of the state have been established and formation of the state customs procedures concept in the national legal science has been described. The author’s interpretation is proposed along with a delineation of the categories of «optimization» and «modernization» of the customs houses as the means for reforming the state customs procedures. The legal principles and the procedures of establishment, re-organization and liquidation of the customs bodies of the State Fiscal Service of Ukraine have been analysed in terms of optimization and modernization of the institutional base of the state customs procedures. Comprehensive analysis of the legal principles underlying staffing technology of the customs bodies of the State Fiscal Service of Ukraine has been made including specific peculiarities of such measures as «rotation», «transfer» and «one-level shifting» of officers. Administrative and legal basics underlying the system of the customs bodies of the State Fiscal Service of Ukraine and of the appropriate system of administrative procedures aimed at accomplishment of the customs procedures have been described. Classification of the administrative procedures used by the customs bodies of the State Fiscal Service of Ukraine when executing the legally entrusted functions has been proposed and the contents of such procedures defined. Current approaches to customs control, being an instrument to accomplish the state customs procedures, were characterized and the directions for improvement of such procedures were defined. The structure of the customs procedures when clearing commodities was determined and the methods and means to improve them were described. Studied are the modern ways to facilitate the customs procedures and harmonize them with the international legal standards and the EU legislation, including specific implementation of the analysis and risk evaluation system, peculiarities of control over correct evaluation of the customs value of commodities that are imported in the customs territory of Ukraine as well as implementation of the «free pratique». Conceptual aspects of the preferential trade regime implementation in Ukraine are revealed and the problematic aspects and prospects for modernizing the administrative and legal concept of the state customs procedures at the current stage of state building with due account of the global trends of the world trade development and requirements imposed by the national security have been characterized. Analysis of the effective legislation of Ukraine relating to the state customs procedures made the basis for submitting specific proposals on development of a single balanced approach to lawmaking and administration of the law in the state customs procedures sphere, and the scientifically substantiated and integral model of administrative and legal concept of the state customs procedures realization.
дис. ... д.ю.н. : 12.00.07
Федотов О.П. Адміністративно-правова концепція здійснення державної митної справи: теорія та практика: дис. ... д-ра. юрид. наук : 12.00.07 / Федотов Олексій Павлович. – Одеса, 2016. – 457 с.
Keywords: адміністративно-правова концепція здійснення державної митної справи; вільна практика; державна митна справа; Державна фіскальна служба України; концепція; концепція правового регулювання митних процедур; концепція правового регулювання порядку утворення та реорганізації органів митного спрямування Державної фіскальної служби України; концепція правового регулювання технології кадрового забезпечення органів митного спрямування; митниця; митна вартість; органи та підрозділи митного спрямування; преференційний торговий режим; уповноважений (схвалений) експортер; административно-правовая концепция осуществления государственного таможенного дела; свободная практика; государственное таможенное дело; Государственная фискальная служба Украины; концепция; концепция правового регулирования таможенных процедур; концепция правового регулирования порядка образования и реорганизации органов таможенного направления Государственной фискальной службы Украины; концепция правового регулирования технологии кадрового обеспечения органов таможенного направления; таможня; таможенная стоимость; органы и подразделения таможенного направления; преференциальный торговый режим; уполномоченный (одобренный) экспортер; administrative and legal concept of the state customs procedures implementation; free practique; state customs procedures; State Fiscal Service of Ukraine, concept; concept of legal control of the of the customs procedures; concept of the legal control of establishment and re-organization of the customs bodies of the State Fiscal Service of Ukraine; concept of the legal control of the technology applied for staffing the customs bodies; customs house; customs value; customs bodies and divisions; preferential trade regime; authorized (approved) exporter